Integrating network pharmacology prediction and experimental investigation to verify ginkgetin anti-invasion and metastasis of human lung adenocarcinoma cells via the Akt/GSK-3β/Snail and Wnt/β-catenin pathway - Liu, Kaile; Fu, Xiaojie; Wang, Zhongqi; Yang, Lian; Yang, Jia; Deng, Haibin (Frontiers in Pharmacology, 2023)
Ginkgetin (GK) is a non-toxic natural biflavone that exerts anticancer effects through cell cycle arrest, triggering apoptosis, inducing autophagy, and preventing angiogenesis. However, how GK inhibits the invasion and spread of lung cancer cells remains unknown. Therefore, we constructed and analyzed GK-targeted lung cancer network through network pharmacology methods. Seventy-nine GK anti-lung cancer targets were identified through PPI network analysis. Using a false discovery rate cutoff of 0.05, we conducted a gene ontology (GO) enrichment analysis and discovered that 79 targets were significantly enriched in GO terms; these targets were primarily involved in positively regulating cell migration, making them promising targets for GK in lung cancer treatment. The cancer pathway is one of the most enriched in our Kyoto Encyclopedia of Genes and Genomes pathway enrichment research, showing that all potential targets demonstrated substantial enrichment in 154 pathways. The results of this study demonstrated the inhibitory effect of GK on tumor invasion and metastasis of lung adenocarcinoma cells (A549, H1299 and LLC). The results of in vitro experiments showed that GK had a great inhibitory effect on cell invasion and metastasis of A549 and H1299. In vivo animals GK had a great inhibitory effect on LLC metastasis. The experimental results are consistent with the expected pattern of network pharmacology. The results of this study can be used as a starting point for other mechanistic studies.